COVID-19 vaccination in India: is it in right direction? - Kumar, Ankit; Singh, Mahendra; Semwal, Bheem Dutt (International Journal Of Community Medicine And Public Health, 2022)
Coronavirus disease (COVID-19), is an infectious disease caused by a newly discovered coronavirus (SARS-CoV-2), which has spread rapidly throughout the world. In March 2020, the World Health Organization (WHO) declared the COVID-19 outbreak a pandemic. The pandemic has severely ravaged health systems and economic and social progress globally. In India, 3,36,52,745 confirmed COVID-19 cases and over 4,46,918 deaths have been reported as of 25 Sep 2021. Symptoms of COVID-19 most commonly manifests as fever, dry cough, shortness of breath and tiredness. Most people (80%) experience mild disease and recover without hospitalization, while around 20% may become more seriously affected. While countries, including India, have taken strong measures to contain the spread of COVID-19 through better diagnostics and treatment, vaccines will provide a lasting solution by enhancing immunity and containing the disease spread. In response to the pandemic, the vaccine development process has been fast-tracked. COVID-19 vaccination dry run: just like army drills, dry run is a dummy process that helped the government assesses how ready we are for the COVID-19 immunization at the national level. It also highlighted any shortcomings in the mechanism laid out for the coronavirus vaccine drive so that we can address them before time and avoid any difficulty or problems during the actual immunization process. After administration of vaccine in population and recent research study has been done in India- that efficacy of Covishield vaccine is more than Covaxin vaccine.